The Human Factor Approach to Managerial and Organizational Efficiency and Effectiveness - Adjibolosoo, Senyo (Springer International Publishing, 2018)
This book argues that human factor development is the key to organizational success. The author describes the human factor as the diverse personality characteristics that allow employees within the social institutions to function and remain operational over time. A lack of appreciation for the significance of personality traits in performance has resulted in organizational inefficiency, but Adjibolosoo proposes a framework that analyzes spiritual capital, moral capital, human capital, aesthetic capital, human ability and human potential and addresses any human factor deficiencies. Further, case studies show that employee effectiveness and profitability of organizations can be attained through effective human factor engineering programs. The contents of this book will serve as powerful eye-openers to scholars in HRM as well as leaders and managers looking to achieve and sustain higher levels of productivity, growth, and profitability at work. .